Chicken pox infection in patients undergoing chemotherapy: A retrospective analysis from a tertiary care center in India. Issue 1 (January 2017) - Noronha, Vanita; Ostwal, Vikas; Ramaswamy, Anant; Joshi, Amit; Nair, Reena; Banavali, Shripad D.; Prabhash, Kumar
Summary: There is paucity of data on the incidence, severity and management of chicken pox in patients receiving active chemotherapy for cancer. From October 2010 to October 2011, patients were included in this study if they developed a chicken pox infection during their chemotherapy. The details of patients' cancer diagnosis and treatment along with clinical and epidemiological data of the chicken pox infections were assessed from a prospectively maintained database. Twenty-four patients had a chicken pox infection while receiving chemotherapy and/or radiotherapy. The median age of the patients was 21 years, and two-thirds of the patients had solid tumor malignancies. Overall, eight (33%) patients had complications, six (25%) patients had febrile neutropenia, four (17%) had diarrhea/mucositis, and four (17%) had pneumonia. The median time for recovery of the infection and complications in the patients was 9.5 days (5–29 days), whereas for neutropenic patients, it was 6.5 days (3–14 days). The median time for recovery from chicken pox infections in neutropenic patients was 10 days (5–21 days), compared with 8.5 days (0–29 days) in non-neutropenic patients ( P = 0.84). The median time for recovery from infections was 8.5 days in patients with comorbidities ( N = 4), which was the same for patients with no comorbidities. The clinical presentation and complication rates of chicken pox in cancer patients, who were on active chemotherapy, are similar to the normal population. The recovery from a varicella infection and complications may be delayed in patients with neutropenia. The varicella infection causes a therapy delay in 70% of patients. Aggressive antiviral therapy, supportive care and isolation of the index cases remain the backbone of treatment.